What Time Alone Offers: Narratives of Solitude From Adolescence to Older Adulthood - Weinstein, Netta; Nguyen, Thuy-vy; Hansen, Heather (Frontiers in Psychology, 2021)
Solitude – the state of being alone and not physically with another – can be rewarding. The present research explored the potential benefits of solitude from a pragmatist approach: a ground-up, top-down perspective that is receptive to new knowledge but informed by theory (Morgan, 2007). Participant recruitment was stratified by age and gender, and the sample involved 2,035 individuals including adolescents (13-16 years), adults (35-55 years), or older adults (65+ years). Data were analyzed with a mixed-methods approach. Coded themes from brief narratives about solitude were extracted, and their frequencies (i.e., their salience to participants) were compared across the lifespan. Themes were then correlated with two indicators of well-being in solitude: self-determined motivation for solitude and peaceful mood. Several prominent themes emerge when talking about time spent in solitude. With the exception of feeling competent in solitude, which was described frequently but consistently unrelated to self-reported well-being regardless of age, benefits of solitude tended to shift over the lifespan. Some qualities, such as a sense of autonomy (self-connection and reliance, absence of pressure), were salient and consequential for everyone, but increasingly so from adolescence to older adulthood. Older adults also reported feeling most peaceful in solitude and described their social connection and alienation less frequently, suggesting they see solitude and social time as more distinct states. Findings are discussed in light of existing work on solitude across the lifespan, and theoretical frameworks that spoke well to the data (e.g., self-determination theory; Ryan & Deci, 2017).